2000
DOI: 10.1029/2000jc900060
|View full text |Cite
|
Sign up to set email alerts
|

Bathymetry, stratification, and internal seiche structure

Abstract: Abstract. Internal seiches play a significant role in a broad range of physical, chemical, and biological processes in lakes. A derailed assessmere of the impact of seiching requires an understanding of seiche structure, which is determined by bathymetry and stratification. In this study, internal seiche solutions are evaluated for arbitrary bathymetry and continuous stratification using a two-dimensional numerical model. Formulated in terms of a stream function, the model produces a finite set of linear inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
66
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 31 publications
2
66
0
1
Order By: Relevance
“…Fricker and Nepf (2000) showed that the magnification of currents and the location of a def- inite amplitude maximum somewhere over the middle of the slope depends on the structure of the stratification, unlike the flat-bottom case, where the maximum of bed velocity is always located in the middle of the basin. In similar fashion, the maximum bed velocity in the 3-D case is located away from the middle of the cell, where it would occur in a flatbottom Poincaré wave (Csanady 1967;Antenucci et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fricker and Nepf (2000) showed that the magnification of currents and the location of a def- inite amplitude maximum somewhere over the middle of the slope depends on the structure of the stratification, unlike the flat-bottom case, where the maximum of bed velocity is always located in the middle of the basin. In similar fashion, the maximum bed velocity in the 3-D case is located away from the middle of the cell, where it would occur in a flatbottom Poincaré wave (Csanady 1967;Antenucci et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…16), located on the western slope. To do so, we calculated (following Fricker and Nepf 2000), at the elevation of each thermistor, the time series of temperature fluctuation with respect to the mean temperature profile in Fig. 5 and band passed this at the dominant observed periods, 24 and 12 h. Assuming that changes in temperature are due mainly to vertical displacement (i.e., assuming very small horizontal temperature gradients), the vertical displacement is give by…”
Section: Interaction Of the Wind And The Dominant Natural Modesmentioning
confidence: 99%
See 2 more Smart Citations
“…The height of such well-mixed layers varies between a few meters in lakes and reservoirs (Gloor et al 2000;Hondzo and Haider 2004;Lemckert et al 2004) to several tens of meters in oceans (Caldwell 1978;Lentz and Trowbridge 1991). The turbulent kinetic energy (TKE) required to generate and maintain such mixed layers is usually assumed to be produced by the bottom friction of basin-or large-scale currents (Fricker and Nepf 2000; Wüest et al 2000), shoaling and critical reflection of high-frequency internal waves (Thorpe 1997; Imberger 1998), or the interaction of large-scale currents with rough topography (Rudnick et al 2003).Enhanced mixing along the boundaries has been demonstrated in numerous studies (Macintyre et al 1999; Ledwell et al 2000;Garrett 2003). Moreover, tracer measurements in lakes (Goudsmit et al 1997) and ocean basins (Ledwell and Bratkovich 1995; Ledwell and Hickey 1995) revealed the potential importance of boundary mixing for basin-scale 1 To whom correpsondence should be addressed.…”
mentioning
confidence: 99%